2015
DOI: 10.12932/ap0597.34.1.2016
|View full text |Cite
|
Sign up to set email alerts
|

An association and meta-analysis study of 4 SNPs from beta-2 adrenergic receptor (ADRB2) gene with risk of asthma in children

Abstract: None of the four polymorphisms in ADRB2 gene were associated with a risk of asthma in a current children population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…[ 81 ] CTLA-4 can improve airway hyperresponsiveness and plays an important role in the pathogenesis of asthma. [ 82 ] Our results and Guo et al [ 83 ] found -46 G/A and -79G/C polymorphisms of ADRB2 gene were not associated with a risk of childhood asthma. However, some studies [ 84 , 85 ] indicated that -79G/C polymorphism was associated with a reduced risk for the development of pediatric asthma.…”
Section: Discussionsupporting
confidence: 58%
“…[ 81 ] CTLA-4 can improve airway hyperresponsiveness and plays an important role in the pathogenesis of asthma. [ 82 ] Our results and Guo et al [ 83 ] found -46 G/A and -79G/C polymorphisms of ADRB2 gene were not associated with a risk of childhood asthma. However, some studies [ 84 , 85 ] indicated that -79G/C polymorphism was associated with a reduced risk for the development of pediatric asthma.…”
Section: Discussionsupporting
confidence: 58%
“…Initially, there were 386 potentially relevant publications identified during the literature search. Following primary screening using the study exclusion criteria, a total of 167 publications were eliminated, which resulted in a total of 18 controlled studies that included 2,982 pediatric patients with asthma and 2,651 controls [10,1517,2235]. The main findings of each study are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published controlled clinical have investigated the role of the ADRB2 gene and the gene polymorphisms in the susceptibility to asthma in pediatric patients [10,1517]. However, these studies have reported inconsistent findings, because of the small number of study participants, the presence of clinical heterogeneity, or due to a combination of both factors.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the β 2 -AR gene polymorphisms are associated with individual predisposition to airway hyperreactivity and asthma, variability in response to β 2 -agonists, and the development of resistance to their bronchodilator effect. The link between the Gln27Glu polymorphism in the β 2 -AR gene and the risk of asthma, which was proven in numerous studies, still relates to contradictory and sometimes opposite results in other studies [4][5][6].…”
mentioning
confidence: 98%
“…The most extensively studied and common polymorphic variants of the β 2 -AR gene are Gln27Glu, Arg16Glu, and Thr164lle, which determine the functional features of the receptor associated with asthma phenotypes and the effectiveness of β 2 -agonist treatment [1-3].At present, the β 2 -AR gene polymorphisms are associated with individual predisposition to airway hyperreactivity and asthma, variability in response to β 2 -agonists, and the development of resistance to their bronchodilator effect. The link between the Gln27Glu polymorphism in the β 2 -AR gene and the risk of asthma, which was proven in numerous studies, still relates to contradictory and sometimes opposite results in other studies [4][5][6].Some papers, especially concerning pediatric asthma, also demonstrated that the Gln27Glu polymorphism in the β 2 -AR gene was not associated with a higher risk of asthma in different ethnic groups within general population…”
mentioning
confidence: 99%